2020
DOI: 10.1177/1356766720927777
|View full text |Cite
|
Sign up to set email alerts
|

Tourist attitudes to mega-event sponsors: Where does patriotism fit?

Abstract: The sponsoring of mega-events enables organizations to capitalize on the power of sport to stimulate passionate brand identifications among attendees. However, a critical issue that has not been addressed by scholars is whether the effects of sponsoring mega-events such as the Olympics by a foreign brand will resemble the equivalent sponsorship by a domestic counterpart. In particular, few scholars have investigated attendee perceptions of congruities between event sponsor and self-sponsor brand favorability e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This can be explained, due to several factors: As indicated above, patriotic values highlight the love for your own country, but do not necessarily generate negative feelings, towards foreign brands that represent luxury, social status, cultural proximity, Bartikowski et al (2020); Chang et al (2020); on the other hand, previous studies by Chaudhry et al (2020) have shown that a person can be ethnocentric, and have a loyalty and positive image towards foreign brands, which are very strong brands because they are global brands or because their consumption generates social status, or because their consumption is already daily.…”
Section: Discussion Research Implications and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be explained, due to several factors: As indicated above, patriotic values highlight the love for your own country, but do not necessarily generate negative feelings, towards foreign brands that represent luxury, social status, cultural proximity, Bartikowski et al (2020); Chang et al (2020); on the other hand, previous studies by Chaudhry et al (2020) have shown that a person can be ethnocentric, and have a loyalty and positive image towards foreign brands, which are very strong brands because they are global brands or because their consumption generates social status, or because their consumption is already daily.…”
Section: Discussion Research Implications and Limitationsmentioning
confidence: 99%
“…This can be explained, due to several factors: As indicated above, patriotic values highlight the love for your own country, but do not necessarily generate negative feelings, towards foreign brands that represent luxury, social status, cultural proximity, Bartikowski et al. (2020) ; Chang et al. (2020) ; on the other hand, previous studies by Chaudhry et al.…”
Section: Discussion Research Implications and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Museum (Wang & Wu, 2011). Also, research on other contexts like Company (Wotruba & Breeden, 1973), Event (Chang et al, 2020;Lorgnier et al, 2022;, Festival (Ding & Hung, 2021;Shin et al, 2018), Sports Team (Calabuig et al, 2021;…”
Section: Contexts Of Self-congruity Research (C)mentioning
confidence: 99%
“…PAT was described “as an affective attachment towards the in-group implying feelings of belongingness, responsibility and pride” (Mummendey et al , 2001, p. 160). The existing research on PAT has mainly been in marketing; PAT is shown as an important predictor that impacts an individual’s decision-making process, such as purchasing domestic products (Han, 1988; Ishii, 2009), liking a mega event (Alonso Dos Santos et al , 2019; Chang et al , 2020), supporting sponsors (Chang et al , 2020; Petrovici et al , 2015) and media consumption intention (Brown et al , 2016; Choe et al , 2019). However, the studies on factors (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%